Słowiańszczyzna i świat z perspektywy japońskiej - Janaszek-Ivaničková, Halina (Przegląd Rusycystyczny, 2009)
SLAVDOM AND THE WORLD SEEN FROM A JAPANESE PERSPECTIVE Summary The purpose of this article is to draw attention to the special way of viewing the Slavic regions in the continental and global contexts as interpreted by the Japanese scholars, who are implementing, as part of broad international cooperation, a program of spatial studies on regional transformations taking place after 1989 in Eurasia, or on the continent of which Slavdom is an integral part (the breakup of the Soviet mega-area, the rise of new Slavic countries, the entry of some of them into the meso-area of the European Union, etc.). Having analyzed the dynamics of the so-called mega- and meso- areas with the fl ywheel of global capitalism behind them, the Japanese authors draw far-reaching conclusions concerning the future self-identifi cation of the Slavic inhabitants of Eastern Europe from pro-Western to Central-European, from Central-European to European and Asian. At the end of this deve-lopmental process, they believe, the inhabitant of Eurasia will consider him/herself not only European but also Eurasian, and s/he will ultimately fully identify with Eurasia, considering him/herself Eurasian only. The author asks the question about the rationality and range of these predictions. To what extent it is wishful thinking, and to what degree it is the accurate understanding of the direction of globalization tendencies taking place on the common continent of Eurasia. СЛАВЯНСКИЕ СТРАНЫ И МИР С ЯПОНСКОЙ ТОЧКИ ЗРЕНИЯ Резюме Настоящая статья старается обратить внимание на то, как видят славянский мир в кон-тинентальном и глобальном контексте японские ученые, которые, в сотрудничестве с мно гими учеными с разных стран, реальзуют программу региональных изменений, проиходящих с 1989 г. в Евразии, т.е. на континенте, которого славянске земли явля ются интегральной частью (распад советского мегаареала, образование новых сла вянский стран, интеграция некоторых среди них с Европейским Союзом и т.п.). Анализа динамики т.н. мега- и мезорегионов, которые являются косвенным результатом глобального капитализма, при водит японских авторов к утверждению, что самоидентификация славян Восточной Европы с прозападной на центрально-европейскую, а потом с центрально-европейской на азиатскую. С течением времени, как утверждают японскийе исследователи, житель Евразии почувствует себя „не столько Европейцем, но Евроазиатом”, а самом конце этого процесса станет уже исключительно Евроазиатом.Автор статьи ставит вопрос, касающийся рациональности и размеров этих прогнозов. Спрашивает, в какой мере они вытекают из ожиданий и желаний японцев, а в какой мере оно является управомоченным утверждением, вытекающим из анализа направления глобализационных тенденций развития Евразийского мегаконтиннта.